Your best year ever : a 5-step plan for achieving your most important goals - Hyatt, Michael, 1955- (Baker Books, a division of Baker Publishing Group, 2023)
"New York Times bestselling author shares a powerful, proven, research-driven system for setting and achieving your goals. If you're tired of not seeing progress in your personal, intellectual, business, relational, or financial goals, it's time for you to have your best year ever!"--